Using a two-sample mendelian randomization analysis to explore the relationship between physical activity and Alzheimer’s disease - Zhang, Bowen; Huang, Xiaowen; Wang, Xiliang; Chen, Xiaorui; Zheng, Caifang; Shao, Weihao; Wang, Gaili; Zhang, Weidong (Scientific reports, 2022)
Evidence from previous epidemiological studies on the effect of physical activity on the risk of Alzheimer’s disease (AD) is conflicting. We performed a two-sample Mendelian randomization analysis to verify whether physical activity is causally associated with AD. This study used two-sample Mendelian randomization (MR) analysis to estimate the association between physical activity (including overall activity, sedentary behavior, walking, and moderate-intensity activity) and AD. Genetic instruments for physical activity were obtained from published genome-wide association studies (GWAS) including 91,105 individuals from UK Biobank. Summary-level GWAS data were extracted from the International Genomics of Alzheimer’s Project IGAP (21,982 patients with AD and 41,944 controls). Inverse Variance Weighted (IVW) was used to estimate the effect of physical activity on AD. Sensitivity analyses including weighted median, MR-Egger, MR-PRESSO, and leave-one-out analysis were used to estimate pleiotropy and heterogeneity. Mendelian randomization evidences suggested a protective relationship between walking and AD (odds ratio (OR) = 0.30, 95% confidence interval (CI), 0.13–0.68, P = 0.0039). Genetically predicted overall activity, sedentary behavior, and moderate-intensity activity were not associated with AD. In summary, this study provided evidence that genetically predicted walking might associate with a reduced risk of AD. Further research into the causal association between physical activity and AD could help to explore the real relationship and provide more measures to reduce AD risk.